SONGKET NAGARI UNGGAN KAJIAN BENTUK DAN FUNGSI - Yondra, Nofri; nofrial, nofrial; Rahmi, Hijratur (Relief : Journal of Craft, 2024)
The research conducted in Nagari Unggan aims to describe the form of motifs and product forms produced by songket craftsmen, as well as to find out what the functions of Nagari Unggan songket are. The theory used in this study is the theory of form, function, songket, motifs, clothing and products, while the method used in this study is qualitative, data collection is carried out by observation, documentation and interviews. Songket Unggan has 30 motifs that are typical of the area, 15 motifs are very popular in the market, namely the Unggan thousand hills, lansek manih, tampuak manggi, cantik manis, cemara, lotus, chain, kelok lontiak, itiak pulang patang, makota, bintang, rangkiang, rumah gadang, pucuak rebung and pintuek motifs. Songket Nagari Unggan also uses other regional motifs, namely motifs from Pandai Sikek, Halaban and Silungkang. Products produced by songket craftsmen in Nagari Unggan include Koko shirts, skirts or kodek, kuruang shirts or tunics, gamis shirts, jackets, tingkuluak, shawls, scarves, deta, outer, shirts, wallets, bucket hats, peci, bags, and household items such as tablecloths. The function of songket in Nagari Unggan is used for traditional events, and parties, and also used as everyday clothing.